Role of ion bombardment, film thickness and temperature of annealing on PEC activity of very-thin film hematite photoanodes deposited by advanced magnetron sputtering. (20th July 2016) - Kment, Stepan; Cada, Martin; Hubicka, Zdenek; Krysa, Josef; Kmentova, Hana; Olejnicek, Jiri; Cilova, Zuzana Zlamalova; Zboril, Radek
Abstract: A High Power Impulse Magnetron Sputtering (HiPIMS) system was used for deposition of hematite thin films. Ion flux density on substrate was studied for different pulse discharge current densities corresponding to different pulsing frequencies of cathode voltage. Total thermal power flux density on substrate was investigated for the same plasma conditions as ion flux density was measured. Our findings revealed the pulse ion flux density on substrate linearly increases with pulse discharge current density whilst the total thermal power density decreases on about 50% when discharge pulsing frequency falls from 50 kHz to 100 Hz. Our previous investigation proved that the change in the discharge pulsing frequency has significant influence on microstructure of deposited hematite thin film. Results of our study imply that magnitude of the ion flux density on substrate leads to highly textured hematite thin film oriented along the desired (110) plane. Nevertheless the ion flux density on substrate is not substantial contribution to the total energy balance on substrate. Other elementary processes taking place on substrate probably can play a significant role in hematite thin film formation. The highest photocurrents of 0.86 mA cm −2 at 0.55 V and 0.99 mA cm −2 at 0.7 V vs. Ag/AgCl was revealed for the HiPIMS deposited films having the thickness of 25 nm and after the thermal treatment at 750 °C for 30 min. The photocurrents of 0.7 mA cm −2 at 0.55 V and 0.82 mA cm −2 at 0.7 V vs. Ag/AgCl of hematite films annealed at 650 °C for 30 min were reached when the voltage bias was applied to the FTO substrate during the deposition. Highlights: The hematite very thin (∼25 nm) photoanodes were fabricated by HiPIMS. The higher ion flux on substrate, the better activity towards solar water oxidation. Photocurrents of 1 mA at 0.7 V vs. Ag/AgCl were reached after annealing at 750 °C. Substrate voltage biasing during HiPIMS deposition improves overall photoefficiency.